Simulink Implementation of the Data Distribution Service for Vehicular Controllers on Top of GBE and AFDX. (1st February 2021) - Takrouni, Manel; Bouhouch, Rim; Hasnaoui, Salem
Abstract: Vehicular networks have seen major changes in the past few years in order to offer reliable and real-time capable high-speed data transmission between electrical and mechatronic components to map current and future innovative functions into distributed systems within automotive applications. In the same context, the real-time middleware data distribution service (DDS) is an appropriate alternative for the standard vehicular middleware considering that it handles quality of service (QoS) parameters including real-time ones. In this paper, we are proposing a new approach for DDS implementation and integration into the vehicular system by creating a model-based design blocks. To validate this implementation, we have used the case of the Society of Automotive Engineers (SAE) vehicle benchmark as a simulation and test model. Therefore, we designed a Simulink vehicle as specified by SAE benchmark. Then, we have introduced a new methodology to link each module to a Simulink DDS blockset. The goal of this approach is to facilitate the use of DDS with vehicular controllers and to reduce the deployment and configuration complexities associated with DDS. It will also enable distributed real-time embedded systems developers to concentrate more on the business logic of the application instead of the low-level implementation details. The final developed architecture has been tested using three different types of real-time networks: FlexRay, Gigabit Ethernet and AFDX, to demonstrate that real-time application's QoS are always met using this model.